Interleukin-33 regulates hematopoietic stem cell regeneration after radiation injury - Ping Huang; Xiangyong Li; Ying Meng; Baohong Yuan; Tao Liu; Mengya Jiao; Xiaodi Wang; Yunjun Liu; Hui Yin (Stem Cell Research & Therapy, 2019)
Abstract Background IL-33 is a pleiotropic cytokine of the IL-1 family, which has been reported to implicate in both innate and adaptive immune responses. Recent studies suggest IL-33 is crucial for regulation of myelopoiesis and myeloid cell activity. Here, we explore the potential effect of IL-33 against hematopoietic injury after total body irradiation (TBI). Methods C57BL/6 mice were irradiated with a sublethal dose of radiation (600 cGy) and treated with IL-33 at a dose of 3 μg/dose i.p. once a day for seven consecutive days. H&E staining was used to determine the bone marrow cellularity. A flow cytometer was used to quantify the hematopoietic stem cell (HSC) population, cell proliferation, and apoptosis. The colony-forming assay was used to evaluate the clonogenic function of HSCs. RT-qPCR was used to determine the expression of apoptosis-associated genes. Results Bone marrow HSCs from wild-type mice expressed functional IL-33 receptor (ST2), and treatment with IL-33 promoted the recovery of the HSC pool in vivo and improved the survival of mice after TBI. Conversely, mice with ST2 deficiency showed decreased HSC regeneration and mouse survival after TBI. Of note, IL-33 reduced radiation-induced apoptosis of HSCs and mediated this effect through repression of the p53-PUMA pathway. Conclusions IL-33 regulates HSC regeneration after myelosuppressive injury through protecting HSCs from apoptosis and enhancing proliferation of the surviving HSCs.